JPEGHRepairKit: Corrupted JPEG Header Repair Kit using Header Substitution Method with JPEG Carving Feature - FARHANA SYAMIMI BINTI MISRAN,; NURUL AZMA BINTI ABDULLAH, (Applied Information Technology And Computer Science, 2025)
Recovering damaged image files is essential in digital forensics for determining and finding evidence, as corrupted JPEG files can delay investigations. This project aims to develop JPEGHRepairKit, a tool for repairing corrupted JPEGs, using Object-Oriented System Development methodology and Microsoft Visual Studio. The study employs header substitution methods to regain access to damaged JPEG files by focusing on their headers. The results indicate that JPEGHRepairKit effectively recovers images with header-related corruption, providing a significant contribution to digital forensic investigations. Future work may explore enhancements to the tool's algorithms and extend its capabilities to other image formats.